Evaluation of flexible pavement distresses-A Case Study of Northern Bypass Peshawar, Pakistan - Ali, M. (Institute of Electrical and Electronics Engineers Inc., 2021)
Pavement degradation results due to both ecological and structural reasons. It is never easy to sustain the road to the exact specifications that were kept at the time of opening. With the passage of time, the pavement structure deteriorates. Hence, pavement distresses like different kinds of cracks, holes, and undulations start appearing. Maintenance is an essential practice in providing for the prolonged performance and the aesthetic manifestation of an asphalt pavement. Pavement maintenance aims to rectify deficiencies triggered by distresses and protect the pavement from further damage. The present research seeks to evaluate the distresses produced in flexible pavement. The northern bypass road located in Peshawar, Pakistan, was under consideration as a case study. A methodology was proposed to investigate the pavement condition, consisting of a manual survey performed as per the ASTM D 6433 standard. The pavement was split into different sections. Each section was further divided into sample groups. The kind and severeness of sample distresses were evaluated by visual scrutiny of the pavement sample groups, and the amount of each distress was quantified. This process required a crew of two engineers. It was inferred that identifying defects and knowing their roots could help improve rating pavement conditions and select cost-effective repairing methods. The periodic inspection was found to be necessary for providing current and valuable evaluation data. It was recommended that ratings should be updated every year. Â© 2021 IEEE.